Engineering Geology - Lwisa, Essa; Arman, Hasan (IntechOpen, 2021)
This book focuses on topics closely related to geological structures and hazards associated with rock constructions. It studies in detail geological masses, field tests, and ground improvement. Chapters discuss various geological investigations in the road, dam, and water reservoir construction.